Resolution No. 177 of the year 2019 Regarding forms of Financial Lease and Factoring Contracts = قرار رقم 177 لسنة 2019 بشأن نماذج عقود التأجير التمويلي والتخصيم / Financial Supervisory Authority - Egypt. Financial Supervisory Authority (2025)
Financial regulatory authority resolution no. 177 of the year 2019 on 19/2/2019 regarding forms of financial lease and factoring contracts – الهيئة العامة للرقابة المالية قرار رقم 177 لسنة 2019 بتاريخ 19/2/2019 بشأن نماذج عقود التأجير التمويلى والتخصيم